Training foreign language teachers : - Wallace, Michael J. (Cambridge University Press, 1991)
The notion of the teacher as "reflective practitioner" is gaining ground as a powerful concept in teacher education and teacher development. One of the strengths of this approach is that it draws on the experience of a wide range of professions. Another is that it can help break down the gap between theory and practice that is all too often a major source of criticism of teacher education courses. The concept of the reflective practitioner can be applied to many aspects of teacher education including teacher supervision, teaching practice, microteaching, action research, groupwork, teacher assessment, and course design. Training Foreign Language Teachers deals with this important topic in a very lucid and straightforward way. It contains many suggestions for practical work and discussion, and numerous applications to actual situations, including an extended case study. The activities are firmly placed within the framework of a coherent approach to language teacher education. This book is aimed at anyone in the area of foreign language teaching who is engaged in designing, running or taking part in any of the following kinds of professional activities: teacher education courses, in-service training courses, supervision or inspection programs, advisory programs for teachers, staff development programs, and self-development programs. Training Foreign Language Teachers will be ideal as a core-text for MA courses with a teacher education focus.